2011
DOI: 10.5539/ijef.v3n3p227
|View full text |Cite
|
Sign up to set email alerts
|

Does A Long-Run Relationship Exist between Agriculture and Economic Growth in Thailand?

Abstract: This empirical study investigates the causality between agriculture and economic growth in Thailand over the period of 1961 to 2009. A Granger causality approach and the Wald (χ 2 ) coefficient statistic are utilized to reveal a long-run causal relationship and impact transmission between the variables. Based on the time series analyses, a long-run relationship and size impact are detected running from agriculture to economic growth, and vice versa. These findings including with the generalized variance decomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Many researchers (Haleem et al, 2005;Stiglitz, 2007;Shirazi and Manap, 2004;Raza et al, 2012;Jatuporn et al, 2011) believe that agriculture can salvage the declining economy under unstable global economic conditions. Avocado, apple, mango and orange production in South Africa over the decade has shown good growth trends.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers (Haleem et al, 2005;Stiglitz, 2007;Shirazi and Manap, 2004;Raza et al, 2012;Jatuporn et al, 2011) believe that agriculture can salvage the declining economy under unstable global economic conditions. Avocado, apple, mango and orange production in South Africa over the decade has shown good growth trends.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a relatively large number of empirical studies evaluating the theoretical link between agricultural transformation and economic growth, but there is no consensus among scholars. Some economists maintain that agricultural sector is a crucial part of economic growth (Jatuporn et al, 2011;Xuezhen and Gaofeng, 2010;Rostow, 1986). Meanwhile others believe that agricultural sector does not have significant correlation with economic growth (Tiffin and Irz, 2006;Tsakok and Gardner, 2007).…”
Section: Theorymentioning
confidence: 99%
“…Therefore, increased agricultural productivity would be the initiator of industrialization (Dethier and Effenberger, 2011). Jatuporn et al (2011) investigated the long run relationship between agriculture and economic growth for Thailand between 1961 and 2009. The study findings revealed a long run relationship between agriculture and economic growth and concluded that policy makers should regard agriculture as playing an important role in enhancing economic growth.…”
Section: Introductionmentioning
confidence: 99%